A Study on Green Human Resource Management in Conjunction with the Sustainability of Corporate Environments - Bajpai, Navodit (Journal of Advanced Research in HR and Organizational Management, 2020)
The transition toward industrialization, which leads to growth in business output, technology and other business activities, is one of the primary drivers of contemporary living across the world. It is not only a growth in human sustainability but also an increase in its level of life in the world, despite the fact that it is the result of increases in ecological dangers to the activities of human beings. Therefore, at this time, people need to make use of environmentally green practices in order to safeguard the environment of the world as well as the most non-renewable resources of the planet and human. Provisions such as green personnel, green professions and green occupations are becoming more commonplace in present’s world. The business world is becoming more globalized and concurrently, the business is undergoing a transition from an outdated financial structure to a contemporary capacity-based economy that is green to investigate the environmentally responsible parts of the organization’s operations. The “green revolution,” also known as “going green,” “ecological protection” or “environmental sustainability,” “sustainable standard of living,” “caring for our earth,” and a number of other similar concepts, have evolved into natural phenomena that are easily visible in our day-to-day lives. At the present time, Green Human Resource Management, also known as GHRM, has developed into a vital business strategy for big corporations. This is the case in companies where the Human Resource Departments take an active role in making the workplace more environmentally friendly. This paper focuses primarily on the numerous green human resource policies and practices with corporate environmental sustainability and data obtained from secondary accessible sources. It provides an explanation of the essential functions that next-level thinking of a new population of people plays in terms of green technology and knowledge. In addition to this, the study contributes to the existing body of literature by addressing the trajectory of the development of various environmentally green functions. In conclusion, the paper presents a few potentially fruitful HR initiatives that green businesses should use to rescue both the environment and people.